The Impact Of Digital Service And Innovative Work Behavior On Employee Performance : The Mediating Role Of Job Satisfaction - Harsaningsih, Harsaningsih; Sulistyowati, Indah; Isnaeni, Yuli; Sukandar, Agus; Mursid, Ali (Magister Manajemen STIE Bank BPD Jateng, 2025)
This study investigates